The depth of follicular extension in actinic keratosis correlates with the depth of invasion in squamous cell carcinoma: implication for clinical treatment. (23rd March 2018) - Fernández‐Figueras, M.T.; Saenz‐Sardà, X.; Vargas, P.; Thompson, C.T.; Carrato, C.; Puig, L.; Ferrándiz, C.; Ariza, A.
Abstract: Background: Actinic keratosis (AK) may show extension down follicles, not only in cases with full‐thickness epidermal atypia ('bowenoid' AK), but also in cases with atypia limited to the epidermal basalis. Previous studies have demonstrated that, in bowenoid AK, follicular extension is usually superficial, being limited to the upper follicular segment. Little is known about the depth of follicular involvement in cases of invasive squamous cell carcinoma of the skin (iSCC) arising from AK and the role of the follicle in iSCC pathogenesis. Objective: This study investigated the relationship between follicular extension of atypical keratinocytes in an AK and the development of iSCC from the follicular wall. The depth of follicular extension was correlated with the depth invasion of iSCC. Differences between the differentiated and classical pathways of iSCC were also examined. Methods: We performed a retrospective histologic review of 193 biopsy specimens of iSCC with an associated AK. We assessed the presence and depth of follicular extension of atypical keratinocytes in the AK, using tumour (Breslow) thickness and the follicular unit level (infundibular, isthmic and subisthmic), as well as iSCC being present directly adjacent to the follicular basalis. Results: Follicular extension was present in 25.9% of the cases (50 cases), usually extending into the lower follicular segment. The iSCC was present directly adjacent to the follicular basalis in 58% of the cases (29 cases), correlating highly with the depth of follicular extension (infundibular: 3/12; isthmic: 21/33; subisthmic 5/5). Conclusion: The depth of follicular extension of atypical keratinocytes in an AK correlates with the development of depth of invasion of an associated iSCC, irrespective of the pathway of origin. It is therefore important to note the presence and the depth of follicular extension when diagnosing an AK, as follicular extension likely accounts for a significant proportion of recurrent AK and the development of iSCC following superficial treatment modalities.